A TCBD-based AB2-type second-order nonlinear optical hyperbranched polymer prepared by a facile click-type postfunctionalization. Issue 34 (30th July 2020) - Zang, Xiaobo; Liu, Hongtao; Li, Qianqian; Li, Zhong'an; Li, Zhen
Abstract : A double click-type postfunctionalization strategy was successfully designed to prepare an AB2 -type hyperbranched polymer containing highly polarizable tetracyanobutadienyl (TCBD)-based nonlinear optical chromophores. Abstract : So far, second-order nonlinear optical (NLO) hyperbranched polymers have been widely reported; however, introduction of highly polarizable NLO chromophores into them remains a challenge. In this work, we have successfully prepared a tetracyanobutadienyl (TCBD)-based AB2 -type hyperbranched polymer HP3 by integrating double click-type postfunctionalization reactions including Cu(i )-catalyzed Huisgen's 1, 3-dipolar cycloaddition and alkyne-TCNE [2 + 2] cycloaddition. The NLO property of HP3 was carefully studied based on the second-harmonic generation (SHG) measurement, showing a SHG coefficient of 55.6 pm V −1 and good alignment stability with a depoling temperature of 125 °C.